Principles and techniques of biochemistry and molecular biology - Wilson, Keith, 1936-; Walker, John M., 1948- (Cambridge, UK : New York : Cambridge University Press, 2009)
"This best-selling undergraduate textbook provides an introduction t o key experimental techniques from across the biosciences. It uniquely integrates the theories and practices that drive the fields of biology and medicine, comprehensively covering both the methods students will e ncounter in lab classes and those that underpin recent advances and dis coveries. Its problem-solving approach continues with worked examples t hat set a challenge and then show students how the challenge is met. Ne w to this edition are case studies, for example, that illustrate the re levance of the principles and techniques to the diagnosis and treatment of individual patients. Coverage is expanded to include a section on s tem cells, chapters on immunochemical techniques and spectroscopy techn iques, and additional chapters on drug discovery and development, and c linical biochemistry. Experimental design and the statistical analysis of data are emphasised throughout to ensure students are equipped to su ccessfully plan their own experiments and examine the results obtained" --Provided by publisher.
"This textbook integrates the theoretical principles and experimenta l techniques common to all undergraduate courses in the bio- and medica l sciences"--Provided by publisher.
Machine generated contents note: 1. General principles K. Wilson; 2. Cell culture techniques A. R. Baydoun; 3. Centrifugation K. Ohlendieck ; 4. Microscopy S. W. Paddock; 5. Molecular biology, bioformatics and b asic techniques R. Rapley; 6. Recombinant DNA and genetic analysis R. R apley; 7. Immunological techniques R. Burns; 8. Protein structure, puri fication, characterisation and functional analysis J. M. Walker; 9. Mas s spectrometric techniques A. Aitken; 10. Electrophoretic techniques J. Walker; 11. Chromatographic techniques K. Wilson; 12. Spectroscopic te chniques I A. Hofmann; 13. Spectroscopic techniques II A. Hofmann; 14. Radioisotope techniques R. Slater; 15. Enzymes K. Wilson; 16. Principle s of clinical biochemistry J. Fyffe and K. Wilson; 17. Cell membrane re ceptors K. Wilson; 18. Drug discovery and development K. Wilson.
Includes bibliographical references and index.
Keywords: Biochemistry -- Textbooks; Molecular biology -- Textbooks